Determinants of hearing impairment among employees: a case study in a manufacturing industry in Melaka - Ravi, Vinayagamuertty (2021)
This cross-sectional study is intended to determine the relationship between safety dimensions, which are machinery and risk controls towards perception on noise induced hearing loss (NIHL) among workers in one of the manufacturing industries in Melaka. A total of 136 self-administered questionnaires were distributed to the respondents and only 131 respondents had returned the questionnaire at the end of the data collection. Results of One-way ANOVA shown that there was a statistically significant difference between sections and perception on noise induced hearing loss (NIHL). A Pearson’s correlation shown that there was weak, positive significant relationship between machinery and noise induced hearing loss (NIHL). Besides that, there was a fair, positive significant relationship between risk control and the perception on noise induced hearing loss (NIHL). Result from regression analysis revealed that risk control is a significant predictor whereas machinery is not a significant predictor for perception on NIHL. These results suggest that the manufacturing workers are exposed to a high level of noise that can contributes to NIHL. Thus, the company need to protect their workers by complying to the OSH (Noise Exposure) Regulation 2019.